Identification, Cloning And Expressing Of Dna Polymerase Producing Thermophile From Geothermal Water In Malaysia - Hussin, Nurul Akmar (2013)
Aerotolerant anaerobe, Gram-positive with long rod in shape thermophilic bacteria was successfully isolated from Ulu Legong Hot Spring, Kedah, Malaysia in this study. The thermophilic bacteria was successfully isolated from the sediment sample in this study and denoted as 3UL which showed the best growth and well adapted to the laboratory condition compared with other isolates at temperature ranged between 45 to 80oC. Hence, this microbe was chosen for further study. A set of universal primers (F_UNI16S and R_UNI16S) were used to amplify the 16S rRNA gene sequences for ribotyping identification methods. Its 16S rRNA gene sequences (1454 nucleotides) showed very high homology (100%) with Anoxybacillus sp. DR04. The 16S rRNA gene sequence for 3UL has been deposited into “Genbank Data Library” and assigned the accession number JQ951796. Genomic DNA from the isolate was extracted and was used to amplify DNA polymerase I gene sequences. The NREAF2 and XREAR_Fxa were forward and reverse primers used for the DNA polymerase amplification with restriction sites NcoI for forward and XhoI for reverse. The gene was 2,628 bp long and encodes a protein of 876 amino acids in length. The enzyme has molecular mass of 99 kDa and showed sequence homology with DNA polymerase I (94%) from Anoxybacillus sp., (75%) Geobacillus sp., and (74%) Bacillus sp. The gene was over expressed in Escherichia coli BL21 (DE3) by using pET28a(+) as expression vector with his-tag at the C-terminus.